Peningkatan Keterampilan Guru Dalam Penggunaan Aplikasi Microsoft Office di Yayasan Taman Pendidikan Adz-Zikra - Rizalina Rizalina; Elvira Sawitri; Syelfia Dewimarni (Jurnal Pengabdian Masyarakat Dharma Andalas, 2022)
Community service activities are used to improve the skills of YTP-DZIKRA teachers in utilizing Microsoft Office applications as an effort to improve skills and add insight for teachers in an effort to improve the quality of education. . The problems faced by teachers at the Taman Pendidikan Adz-Zikras Foundation today are related to skills in using Microsoft Office offline and the lack of knowledge of using Microsoft Office Online in supporting academic and non-academic activities. Stages of Improving Teacher Skills in Using Microsoft Office at the Taman Pendidikan Adz-Zikra Foundation. divided into 4 (four) stages, namely the preparation stage, the implementation stage, the program evaluation stage and the reporting stage. This service activity gave quite significant results which were marked by the teacher's habit of using and operating Microsoft office, especially Microsoft office word, Microsoft office excel, and Microsoft office powerpoint.